A kind of non-residue high-viscosity environmentally friendly tape glue and preparation method thereof

Through the synergistic effect of dynamic matrix and self-assembled tackifier, combined with nanoparticles and environmental response aids, a dynamic network system is designed, which solves the defects of existing adhesives in terms of viscosity, peeling performance, environmental adaptability and production process, and achieves high initial viscosity, residue-free, environmental adaptability and environmental protection.

CN119736058APending Publication Date: 2025-04-01福建友谊胶粘带集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937068.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing adhesives have defects in their adhesiveness, peeling performance, environmental adaptability and production processes, including unstable viscosity, poor compatibility, peeling residue, unstable environmental performance, high process complexity and insufficient environmental protection.

Method used

Through the synergistic effect of dynamic matrix materials and self-assembled tackifiers, combined with nanoparticle reinforcement materials and environmental response additives, a dynamic network system is designed to achieve a balance between high initial viscosity and peeling-free residual performance, improve environmental adaptability, and simplify the process and use of environmentally friendly raw materials.

Benefits of technology

It significantly improves the adhesive stability, peeling performance, environmental adaptability and production efficiency, solves residual problems and high process complexity, and meets the requirements of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736058A_ABST
    Figure CN119736058A_ABST
Patent Text Reader

Abstract

The invention discloses a non-residue high-viscosity environmentally friendly adhesive tape glue. The glue comprises the following components by mass percentage: 60-80% of a dynamic matrix material, wherein the dynamic matrix material is a modified polyurethane or a thermoplastic elastomer containing a dynamic covalent bond; 15-25% of a self-assembly tackifier, wherein the self-assembly tackifier comprises a modified rosin acid or a short-chain alkyl amide, and forms a dynamic network with the dynamic matrix through a weak interaction formed by hydrogen bonding or π-π stacking; 5-10% of a nanoparticle reinforcement material, wherein the nanoparticles are silicon dioxide or aluminum oxide with a surface silanization treatment, and have a particle size of 10-50 nanometers; 1-5% of an environmental response auxiliary agent, wherein the nanoparticles comprise a thermosensitive polymer or polyvinyl alcohol; and 0.5-1% of an antioxidant and a stabilizer. The balance between high initial viscosity and peeling non-residue performance is achieved, environmental adaptability is significantly improved, and the problems of production complexity and high cost are solved by simplifying the process and applying environmentally friendly raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive tape glue, and specifically relates to a non-residue high-viscosity environmentally friendly adhesive tape glue and a preparation method thereof. Background Art

[0002] Adhesives are widely used in the fields of industry, medical treatment, electronics, automobiles, etc., especially high-performance and environmentally friendly adhesives play an important role in high-demand scenarios such as optical protective films, electronic product components, and medical dressings. However, adhesives in the prior art still have many defects and deficiencies in terms of viscosity, peeling performance, environmental adaptability, and production process.

[0003] 1. Unstable viscosity and poor compatibility

[0004] Existing adhesives usually use a dynamic matrix and a tackifier to improve adhesion performance. However, due to the chemical or physical incompatibility between the dynamic matrix material and the tackifier, the viscosity of the adhesive is easily fluctuated, thereby affecting its use effect. Especially on rough surfaces or low surface energy materials (such as polytetrafluoroethylene, silicone rubber), the adhesion performance is insufficient, which limits the application range of the adhesive. In addition, the microcapsule tackifier design commonly used in the prior art, because the capsule shell is easily broken during mixing and storage, causes the tackifier to be released prematurely, further reducing the stability and service life of the adhesive.

[0005] 2. Insufficient peeling performance and residual problems

[0006] High initial tack and no residue after peeling are key performance indicators of adhesives in high-demand fields such as optical protective films and electronic component assembly. However, existing adhesives are prone to residue during the peeling process and are difficult to meet the requirements of clean peeling. In addition, traditional designs are difficult to achieve a balance between high initial tack and no residue after peeling, and the technical level of peel force regulation needs to be improved.

[0007] 3. Poor environmental adaptability

[0008] Existing adhesives have poor performance stability under extreme environmental conditions (such as high temperature, low temperature, and humidity). Dynamic matrix materials are prone to decomposition or loss of viscosity in high temperature environments, and may become brittle in low temperature environments, resulting in a significant decrease in adhesion performance. These problems limit the widespread application of adhesives in complex scenarios such as automotive interiors, aerospace, and outdoor equipment.

[0009] 4. Complex preparation process and high cost

[0010] In the prior art, the microencapsulation design of tackifiers requires complex emulsion polymerization or spraying processes, which have long production cycles, high equipment requirements and high costs. In addition, during the production process, the microcapsule shell is easily broken by shear force, resulting in a decrease in process yield and further increasing production costs.

[0011] 5. Not environmentally friendly enough

[0012] Traditional adhesives often use petrochemical-based raw materials and solvent-based production processes, which have a significant impact on the environment. The disposable product format causes waste of resources and is not in line with the current development trend of green manufacturing and sustainable development.

[0013] 6.Technology development needs

[0014] With the continuous advancement of industrial technology, high-performance environmentally friendly adhesives need to meet the following requirements at the same time:

[0015] Strong adhesion on rough surfaces and low surface energy materials;

[0016] No residue left after peeling, and can adapt to various peeling conditions;

[0017] Stable performance in extreme environments such as high temperature, low temperature, and humidity;

[0018] The preparation process is simple, the production cost is low, and it is suitable for large-scale industrial production;

[0019] Using environmentally friendly raw materials and solvent-free technology, it meets green environmental protection requirements. Summary of the invention

[0020] The purpose of the present invention is to provide a residue-free, high-viscosity, environmentally friendly tape glue and a preparation method thereof. A dynamic network system is designed through the synergistic effect of a dynamic matrix material and a self-assembly tackifier, combined with a nanoparticle reinforcement material and an environmentally responsive additive, to achieve a balance between high initial viscosity and peeling residue-free performance, significantly improve environmental adaptability, and solve the problems of production complexity and high cost by simplifying the process and using environmentally friendly raw materials.

[0021] The technical solution adopted by the present invention is as follows:

[0022] A non-residue high-viscosity environmentally friendly adhesive tape glue, the glue comprising the following components by mass percentage:

[0023] Dynamic matrix material: 60-80%, the dynamic matrix material is a modified polyurethane or thermoplastic elastomer containing dynamic covalent bonds;

[0024] Self-assembly tackifier: 15-25%, wherein the self-assembly tackifier comprises modified rosin acid or short-chain alkyl amide, and forms a dynamic network with the dynamic matrix through weak interactions formed by hydrogen bonding or π-π stacking;

[0025] Nanoparticle reinforcement material: 5-10%, the nanoparticles are silicon dioxide or aluminum oxide with surface silanization treatment, and the particle size is 10-50 nanometers;

[0026] Environmentally responsive additives: 1-5%, including thermosensitive polymers or polyvinyl alcohol;

[0027] Antioxidants and stabilizers: 0.5-1%.

[0028] The dynamic covalent bonds in the dynamic matrix material include acylhydrazone bonds, disulfide bonds or other reversible chemical bonds, and the dynamic matrix also contains flexible segments to enhance flexibility.

[0029] The self-assembly tackifier forms a weakly interacting dynamic viscous network with the dynamic matrix through hydroxyl, carboxyl or amino polar functional groups, and the network dissociates itself when peeled off.

[0030] The nanoparticles are surface-modified by a silane coupling agent to improve their dispersibility and adhesion properties in a dynamic matrix.

[0031] Wherein, the environmental response additive includes poly (N-isopropylacrylamide), which is used to adjust the viscosity under temperature change conditions.

[0032] A method for preparing the non-residue high-viscosity environmentally friendly tape glue comprises the following steps:

[0033] Dynamic matrix preparation:

[0034] The polyurethane matrix material and the dynamic covalent bond monomer are mixed in proportion, and copolymerized at 80-120° C. for 2-4 hours under the action of an organic tin or organic titanium catalyst to form a dynamic matrix, which is then cooled for standby use;

[0035] Preparation of self-assembly adhesion promoter:

[0036] The modified rosin acid or short-chain alkyl amide is mixed with a polar solvent in a ratio of 1:2 to 1:5, deionized water is added to promote weak interactions to form a self-assembled network, and the solvent is evaporated by heating to 40-60° C. to obtain a self-assembled tackifier;

[0037] Dynamic matrix and tackifier compound:

[0038] The dynamic matrix and the self-assembly adhesion promoter are mixed in a ratio of 3:1 to 5:1, stirred at 50-70°C for 20-40 minutes, and the silanized nanoparticles are added and stirred for 5-15 minutes to ensure uniform distribution;

[0039] Additive addition and pre-curing:

[0040] Add environmental response additives and antioxidants, stir at a low speed of 200-400 rpm for 5-10 minutes, and pre-cure at 30-50°C for 1-2 hours;

[0041] Final curing:

[0042] The pre-curing mixture is heated to 60-80°C, cured for 2-4 hours, cooled to room temperature and stored to obtain a finished glue.

[0043] The dynamic covalent bond monomers used in the preparation of the dynamic matrix include acylhydrazone bond monomers or disulfide bond monomers, and the addition ratio thereof is 1-10% of the matrix mass.

[0044] In the preparation of the self-assembly tackifier, the mixing ratio of the polar solvent to the tackifier raw material is 1:2 to 1:5, and the solvent volatilization temperature is 40-60°C.

[0045] Wherein, during the mixing process, the mass ratio of the dynamic matrix to the tackifier is 3:1 to 5:1, the stirring speed is 300-500 rpm, and the stirring time is 20-40 minutes.

[0046] Wherein, in the final curing step, the curing temperature is 60-80°C and the curing time is 2-4 hours.

[0047] In view of the shortcomings and deficiencies in the prior art, the present invention significantly improves product performance, adaptability and production efficiency through the coordinated design of dynamic matrix materials, self-assembly tackifiers, nanoparticle reinforcement materials and environmental response additives, and optimizes the preparation process. The specific beneficial effects are as follows:

[0048] 1. Improvements on the unstable viscosity and poor compatibility of existing technologies

[0049] The existing technology lacks synergy between the dynamic matrix and the thickener, and there are chemical or physical incompatibility problems, which lead to fluctuations in viscosity performance. The shell material in the capsule technology is easy to break during the preparation and storage process, resulting in leakage of the thickener, unstable performance, and material waste. The initial adhesion on rough or low surface energy materials is insufficient, which limits the scope of application.

[0050] The present invention innovates the dynamic network self-assembly technology. The self-assembly tackifier forms a dynamic network with the dynamic matrix through weak interactions (such as hydrogen bonds or π-π stacking), enhances adhesion during pressing, and dissociates the dynamic network during peeling to ensure no residue. The incompatibility problem between the matrix and the tackifier is completely eliminated, and the viscosity performance is more stable. At the same time, nanoparticle reinforcement materials are added, and the introduction of silanized nanoparticles significantly improves the adhesion point density and surface adhesion, and enhances the adaptability to rough or low surface energy materials. Not only does it improve the initial viscosity and is suitable for a variety of substrates, but it also enhances the compatibility of the dynamic matrix and the tackifier, solves the problem of viscosity instability, and avoids the material rupture and waste problems of traditional microcapsule technology.

[0051] 2. Improvement of poor stripping performance and residual problems in existing technologies

[0052] In the prior art, adhesives are prone to residue after peeling, which makes it difficult to meet the requirements of clean peeling (such as electronic protective films and medical applications). It is difficult to achieve high initial adhesion and no residue after peeling at the same time.

[0053] The present invention innovates the dynamic covalent bond design of the dynamic matrix. The dynamic matrix regulates viscosity through dynamic covalent bonds such as acylhydrazone bonds or disulfide bonds. When peeled, the bonds dissociate, the dynamic network collapses, and the viscosity is significantly reduced. At the same time, the network dissociation of the self-assembled thickener is achieved. The thickener dynamically assembles and dissociates through weak interactions, and quickly loses viscosity when peeled to avoid residue. Not only is the peeling performance greatly improved, the adhesive can be cleanly peeled on the surface of a variety of substrates, and the balance of high initial viscosity and no residue performance makes it suitable for high-demand scenarios, such as medical wound bonding adhesives and high-precision electronic component protective films.

[0054] 3. Improvement of the insufficient performance of existing technologies in complex environments

[0055] In the prior art, adhesives are prone to lose viscosity or age in environments with high or low temperatures or large humidity changes, and have poor performance stability. Poor environmental adaptability limits their application in special scenarios (such as automotive interiors and aerospace).

[0056] The invention introduces innovative flexible segments, and the dynamic matrix is ​​optimized through the flexible segments, which enhances low-temperature flexibility and high-temperature stability. At the same time, thermosensitive additives such as PNIPAM are introduced for regulation, so that the glue can adaptively adjust the viscosity as the ambient temperature changes. The antioxidant and nanoparticles are synergistically enhanced, the antioxidant prolongs the service life of the glue, and the nanoparticles improve the anti-aging performance of the adhesive. Not only does the adhesive have stable performance in the environmental range of -20°C to 80°C and adapt to a variety of extreme environments, it also meets the application requirements of automotive interiors, aerospace, and outdoor equipment that have strict requirements for high and low temperature performance.

[0057] 4. Improvements to existing technologies with high process complexity and high costs

[0058] Some existing technologies use capsule technology, which is complex to prepare and involves multiple steps such as emulsion polymerization and spraying, with a long production cycle and high costs. In addition, the high shear force during the preparation process can easily destroy the capsule structure, further reducing the production yield.

[0059] The present invention innovates the dynamic network self-assembly to replace the capsule technology. The self-assembly thickener does not require a complicated capsule preparation process, and can be completed by stirring and solvent volatilization, and the process is simple. In addition, combined with the optimization of the step-by-step curing process, the low-temperature pre-curing reduces the damage to the thickener by shear mixing, and the high-temperature final curing improves the consistency of product performance. Combined with the reasonable parameter range design, a clear temperature, time and ratio range (such as curing temperature 60-80°C, stirring time 20-40 minutes) is provided to enhance the process controllability and repeatability. The preparation process is significantly simplified, the production efficiency is improved, and it is suitable for large-scale industrial production. The production cost is reduced and the market competitiveness of the product is improved.

[0060] 5. Improve the environmental performance of existing technologies

[0061] The present invention adopts environmentally friendly raw materials and uses natural tackifiers such as modified rosin acid to reduce dependence on petrochemical raw materials. A solvent-free process is adopted, and the glue preparation adopts a solvent-free system to avoid environmental pollution. In addition, the prepared tape has the characteristic of repeated use. After the adhesive is peeled off, the dynamic network returns to the initial state and can be reused, reducing resource waste. The product is more environmentally friendly, meets the requirements of green manufacturing and sustainable development, and reduces the cost and resource consumption of one-time use.

[0062] The present invention has broad market application potential and can be used in multiple fields such as industry, medical treatment, aerospace, etc., and plays an important role in promoting the development of adhesive technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0064] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0065] See also Figure 1 , this invention relates to a non-residue high-viscosity environmentally friendly tape glue and its preparation method:

[0066] 1. Glue formula design

[0067] The present invention provides a non-residue high-viscosity environmentally friendly adhesive tape glue, the formula design of which realizes a highly efficient combination of a dynamic matrix, a self-assembly tackifier, a nanoparticle reinforcement material, an environmental response additive, an antioxidant and a stabilizer, as follows:

[0068] 1.1 Dynamic matrix material

[0069] Mass ratio: 60-80%.

[0070] Material composition:

[0071] Modified polyurethane: By introducing dynamic covalent bonds such as acylhydrazone bonds and disulfide bonds, the matrix is ​​endowed with dynamic viscosity regulation capabilities. These dynamic covalent bonds can be reversibly broken and reorganized under the action of external forces, thereby achieving viscosity regulation.

[0072] Flexible chain segment: The introduction of polyether polyols or polyester polyols can increase the flexibility of the molecular chain and improve the low-temperature toughness and high-temperature stability of the dynamic matrix.

[0073] Thermoplastic elastomers (such as SBS): provide additional mechanical property enhancement and ensure the overall toughness of the dynamic matrix under dynamic stress.

[0074] 1.2 Self-assembly adhesion promoter

[0075] Mass ratio: 15-25%.

[0076] Material composition:

[0077] Modified rosin acid: Modified by hydroxyl or carboxyl groups, it forms hydrogen bonds and other weak interactions with the dynamic matrix, providing the core function of improving viscosity.

[0078] Short-chain alkylamides: form additional sticky network structures through π-π stacking or van der Waals forces, working synergistically with the dynamic matrix.

[0079] When the self-assembling tackifier is used in glue, it forms a dynamic viscous network through weak intermolecular interactions (such as hydrogen bonds and π-π stacking), which enhances adhesion during pressing, while the network quickly dissociates during peeling to ensure no residue.

[0080] 1.3 Nanoparticle-reinforced materials

[0081] Mass ratio: 5-10%.

[0082] Material composition and mechanism:

[0083] Silica or alumina nanoparticles: The particle size is 10-50 nanometers, treated with silane coupling agent to enhance surface activity.

[0084] The high surface area and surface activity of nanoparticles provide more adhesion sites, working synergistically with the dynamic matrix and adhesion promoter to effectively improve adhesion strength and durability.

[0085] 1.4 Environmentally responsive additives

[0086] Mass ratio: 1-5%.

[0087] Material composition:

[0088] Poly(N-isopropylacrylamide) (PNIPAM): This gives the glue temperature sensitivity, adjusting the adhesive strength when the temperature changes. PNIPAM exhibits reversible swelling and shrinking properties near the critical solution temperature, which affects the adhesiveness.

[0089] Polyvinyl alcohol: Enhances the mechanical properties and resistance to environmental aging of the glue.

[0090] 1.5 Antioxidants and Stabilizers

[0091] Mass ratio: 0.5-1%.

[0092] Material composition:

[0093] Antioxidants (such as BHT): Delay the degradation of dynamic matrix and viscosity enhancers by capturing free radicals.

[0094] Light stabilizers (such as HALS): They increase the service life of glue in light environments by stabilizing the degradation process caused by UV rays.

[0095] 2. Preparation method

[0096] 2.1 Dynamic matrix preparation

[0097] Raw material preparation: The polyurethane matrix material is mixed with a dynamic covalent bond monomer (such as an acylhydrazone bond monomer or a disulfide bond monomer) in a ratio of 1-10% of the matrix mass.

[0098] Reaction conditions: Under the action of organic tin or organic titanium catalyst, stir and react at 80-120℃ for 2-4 hours.

[0099] Dynamic covalent bonds are formed through condensation reactions or redox reactions under the action of catalysts, and reversible chemical bonds are embedded in the molecular structure, giving the dynamic matrix material a unique viscosity regulation function.

[0100] After the reaction was completed, the mixture was cooled to room temperature to obtain a dynamic matrix.

[0101] 2.2 Preparation of self-assembly adhesion promoter

[0102] Raw material preparation: Mix the modified rosin acid or short-chain alkyl amide with a polar solvent (such as ethanol or acetone) in a ratio of 1:2 to 1:5 and stir evenly.

[0103] Assembly process: Deionized water is added to the mixed solution to promote weak interactions to form a self-assembled network.

[0104] The synergistic effect of polar solvent and deionized water promotes the formation of stable self-assembled structures of rosin acid or alkylamide molecules through weak intermolecular forces (such as hydrogen bonds or hydrophobic interactions).

[0105] The mixture is heated to 40-60° C. to evaporate the solvent and obtain self-assembled adhesion promoter particles.

[0106] 2.3 Composite of dynamic matrix and tackifier

[0107] Preliminary mixing: Mix the dynamic matrix and the self-assembly adhesion promoter in a mass ratio of 3:1 to 5:1.

[0108] Stir at 50-70°C for 20-40 minutes.

[0109] Nanoparticle dispersion: Add silanized silicon dioxide or aluminum oxide nanoparticles (5-10% by mass) and continue stirring for 5-15 minutes.

[0110] Nanoparticles form physical or chemical adsorption with dynamic matrix and adhesion promoter molecules through the active groups on their surface, further enhancing the adhesion performance.

[0111] 2.4 Environmentally responsive additives and pre-curing

[0112] Adding additives: adding PNIPAM (mass ratio 1-5%) and antioxidant (mass ratio 0.5-1%), stirring at a low speed (200-400 rpm) for 5-10 minutes.

[0113] PNIPAM is evenly dispersed during the stirring process, forming a synergistic effect with the dynamic matrix and tackifier to improve the environmental responsiveness of the glue.

[0114] Pre-curing: Place the mixture at 30-50℃ for pre-curing for 1-2 hours.

[0115] A preliminary cross-linking network is formed through low-temperature pre-curing, providing uniform molecular distribution for the final curing.

[0116] 2.5 Final curing

[0117] High temperature curing: Heat the pre-cured mixture to 60-80°C and cure for 2-4 hours.

[0118] At high temperature, the dynamic matrix is ​​further cross-linked, and the self-assembled tackifier forms a stable dynamic network with the matrix, ensuring the consistency of the finished product performance.

[0119] Cooling and storage: After curing is completed, cool to room temperature to obtain the finished glue.

[0120] 3. Glue performance test

[0121] Within the parameters of the formula and preparation method, the glue is prepared and made into tape, which is summarized as follows: Residue-free high-viscosity environmentally friendly glue formula table:

[0122]

[0123] Process parameter table of non-residue high viscosity environmentally friendly glue:

[0124]

[0125] No residue high viscosity environmentally friendly glue test data table:

[0126]

[0127]

[0128] Test Materials:

[0129] The solution of the present invention: three groups of samples are prepared according to different process parameters (such as curing temperature and time).

[0130] Mainstream product A: a certain brand of high-performance industrial tape.

[0131] Mainstream product B: a certain brand of environmentally friendly medical tape.

[0132] Test conditions:

[0133] Initial adhesion: According to the standard test method, the tape is attached to the surface of the stainless steel plate and the force required for pulling out is measured under constant pressure.

[0134] Peel force: Peel force was measured in a standard peel test apparatus at 180° peeling.

[0135] Residue rate: The ratio of surface residue after peeling, calculated by image comparison and weighing.

[0136] High temperature resistance: Place the sample in a high temperature box to test performance stability and adhesion changes.

[0137] Low temperature resistance: Place the sample in a low temperature box to test the performance and adhesion changes.

[0138] Stability in wet and hot environment: The viscosity reduction percentage is measured after being placed in a 90% humidity, 40°C environment for 48 hours.

[0139] Purpose of the test:

[0140] The high initial viscosity, no residue, environmental adaptability and superior performance of the present invention over existing mainstream products are verified.

[0141] Test data analysis

[0142] 1. Initial viscosity comparison

[0143] The initial tack of the solution of the present invention in three tests is higher than that of mainstream products (24.8-25.5N / 25mm, compared with 20.2N / 25mm and 18.9N / 25mm), indicating that the dynamic matrix of the present invention and the tackifier synergistically significantly improve the initial tack, and are suitable for rough and low surface energy materials.

[0144] 2. Peel force comparison

[0145] The peeling force range of the solution of the present invention (9.9-10.3N / 25mm) is significantly better than that of mainstream products (7.8-8.5N / 25mm), indicating that the dissociation ability of the dynamic network ensures smooth peeling and excellent adhesion performance.

[0146] 3. Comparison of residual rate

[0147] The solution of the present invention has very little residue (1%-3%) in three tests, while the residue rates of mainstream products A and B are 15% and 20% respectively. The present invention completely solves the peeling residue problem through weak interaction network dissociation and is suitable for high-demand scenarios (such as medical and electronic protection).

[0148] 4. High temperature resistance comparison

[0149] The high temperature resistance (115-125°C) of the solution of the present invention is much higher than that of mainstream products (85-90°C), which indicates that the introduction of flexible segments and dynamic covalent bonds significantly enhances the high temperature stability.

[0150] 5. Comparison of low temperature resistance

[0151] The solution of the present invention performs well under low temperature conditions (-20 to -30°C), while mainstream products can only reach -10 to -5°C. This shows that the optimization of the flexible segment effectively improves the low-temperature toughness.

[0152] 6. Comparison of stability in hot and humid environments

[0153] The viscosity of the solution of the present invention in a hot and humid environment decreases by only 2.2-2.8%, which is significantly better than mainstream products (8.5% and 10.0%). This indicates that the introduction of environmental responsive additives (such as PNIPAM) improves the performance stability in a hot and humid environment.

[0154] The reasons for analyzing the remarkable excellent performance of the present invention are as follows:

[0155] 1. Contribution mechanism of dynamic matrix

[0156] 1.1 Introduction of dynamic covalent bonds

[0157] The dynamic matrix contains dynamic covalent bonds such as acylhydrazone bonds and disulfide bonds. These bonds can be broken and reformed when subjected to external forces or environmental changes, giving the matrix the ability to dynamically regulate viscosity.

[0158] Because the dynamic covalent bonds strengthen the initial adhesion of the glue during pasting, the dynamic bonds break quickly during peeling, reducing the stickiness and ensuring that there is no residue during the peeling process.

[0159] Therefore, dynamic covalent bonds provide the ability to dynamically regulate viscosity, solving the contradiction between high initial viscosity and zero residue after peeling.

[0160] 1.2 Optimization of flexible segments

[0161] The introduction of flexible chain segments of polyether polyols or polyester polyols increases the molecular freedom of the matrix, giving the dynamic matrix excellent low-temperature flexibility and high-temperature stability.

[0162] Because the flexible chain segments maintain the ability to move between molecules at low temperatures, the matrix is ​​prevented from becoming brittle. At high temperatures, the flexible chain segments absorb heat without thermal decomposition.

[0163] Therefore, the flexible chain segment significantly improves the environmental adaptability of the matrix, allowing the glue to maintain excellent performance in the range of -30°C to 125°C.

[0164] 2. Contribution mechanism of self-assembly thickener

[0165] 2.1 Weak interactions of polar functional groups

[0166] The modified rosin acid or short-chain alkylamide in the self-assembling tackifier forms weak interactions (such as hydrogen bonding and π-π stacking) with the dynamic matrix through polar functional groups such as hydroxyl and carboxyl.

[0167] During pasting, weak interactions enhance the synergy between the tackifier and the substrate, forming a temporary network structure and improving initial adhesion. During peeling, weak interactions dissociate quickly to ensure no residue.

[0168] Therefore, a balance between high adhesion and residue-free peeling is achieved through weak interactions.

[0169] 2.2 Dynamic characteristics of self-assembly networks

[0170] The thickener forms a dynamic network structure under the action of external force, and its assembly and dissociation process is reversible.

[0171] Since the dynamic network is formed quickly during the pressing process, the effective adhesion area is increased and the viscosity is improved. When peeling, the network structure collapses and the viscosity is weakened, thus achieving clean peeling.

[0172] Therefore, the assembly and dissociation ability of the dynamic network further enhances the precision of viscosity regulation.

[0173] 3. Contribution mechanism of nanoparticle-reinforced materials

[0174] 3.1 Enhancement of Surface Activity

[0175] Nanoparticles (such as silica and alumina) undergo silanization treatment to increase their surface activity and provide stronger interfacial interactions with dynamic matrices and adhesion promoters.

[0176] After silanization treatment, the active groups (such as hydroxyl or amine groups) on the surface of the nanoparticles form physical adsorption or chemical bonding with the matrix, thereby increasing the density of adhesion points.

[0177] This enhances the adhesive strength of the glue, especially on rough surfaces and low surface energy materials.

[0178] 3.2 Improve durability

[0179] The nanoparticles provide additional mechanical reinforcement and anti-aging capabilities by being uniformly dispersed in the matrix.

[0180] The presence of nanoparticles prevents the substrate from undergoing large-scale deformation under external forces, thus extending the service life of the glue.

[0181] This significantly improves the adhesive's adhesion durability and environmental resistance.

[0182] 4. Contribution mechanism of environmental responsive additives

[0183] 4.1 Temperature sensitivity regulation

[0184] Environmentally responsive additives, such as PNIPAM, exhibit reversible swelling and shrinkage properties upon temperature changes.

[0185] At low temperatures, the PNIPAM molecular chains are in a swollen state, which enhances viscosity. At high temperatures, the PNIPAM chains shrink, which reduces viscosity fluctuations.

[0186] This enables the glue to adapt to temperature changes and ensures viscosity stability.

[0187] 4.2 Enhanced stability in hot and humid environments

[0188] PNIPAM and polyvinyl alcohol work together to reduce the interference of moisture on viscosity in hot and humid environments.

[0189] Because these additives adjust the adhesion properties of the substrate by absorbing and releasing moisture, they prevent performance degradation in hot and humid environments.

[0190] Therefore, the viscosity remains stable in a high humidity environment, and the viscosity decreases by less than 3%.

[0191] 5. Synergistic mechanism of dynamic matrix and thickener

[0192] 5.1 Collaborative Enhancement of Dynamic Networks

[0193] The dynamic covalent bonds of the dynamic matrix and the weak interactions of the self-assembled adhesion promoter work together to form a dynamic network.

[0194] Since dynamic covalent bonds provide a backbone structure for viscosity regulation, tackifiers fill the dynamic network through weak interactions and enhance adhesion.

[0195] Therefore, the synergistic effect enables the glue to achieve a perfect balance between initial adhesion, no residue after peeling and environmental adaptability.

[0196] 5.2 Dynamic response during peeling

[0197] During peeling, the dynamic covalent bonds break, the self-assembled network dissociates, and the interfacial interaction of the nanoparticles weakens.

[0198] Under the action of external force, the flexible chain segments of the dynamic matrix absorb the stretching energy and reduce the viscosity fluctuation. After the thickener network dissociates, the possibility of residue is reduced.

[0199] The peeling process is therefore smooth and residue-free, ensuring clean peeling results even on sensitive surfaces.

[0200] 6. Contribution mechanism of preparation process to performance

[0201] 6.1 Step-by-step optimization of pre-curing and final curing

[0202] The pre-curing stage ensures the uniform dispersion of the components, and the final curing forms a stable dynamic network.

[0203] Low temperature pre-curing reduces the possibility of uneven dispersion and micro defects. High temperature final curing strengthens the interfacial bonding between the substrate and the tackifier.

[0204] Therefore, the overall performance stability of the glue is improved.

[0205] 6.2 Precise control of temperature and time

[0206] The range of process parameters (e.g., temperature, time) plays a key role in the synergistic effect of the dynamic matrix, adhesion promoter, and nanoparticles.

[0207] Because under the optimal temperature and time conditions, the interaction between the various components is most complete and the performance is optimal.

[0208] Therefore, the optimized process ensures the repeatability of the glue and the reliability of industrial production.

[0209] in conclusion

[0210] The present invention forms a non-residue, high-viscosity, environmentally friendly glue with excellent performance through dynamic regulation of the dynamic matrix, network construction of the self-assembled tackifier, multifunctionality of the nanoparticle-reinforced material, and intelligent regulation of the environmentally responsive additive. The mechanism of its excellent performance includes:

[0211] Synergy of dynamic networks.

[0212] Multi-level interactions between materials (dynamic covalent bonds, weak interactions, nanoparticle interface bonding).

[0213] Dynamic response of environmentally adaptable additives.

[0214] Scientific and reasonable preparation process.

[0215] The present invention has significant technical advantages in terms of viscosity control, peeling performance, environmental adaptability and service life.

[0216] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-residue high-viscosity environmentally friendly tape glue, characterized in that: The glue comprises the following components by mass percentage: Dynamic matrix material: 60-80%, the dynamic matrix material is a modified polyurethane or thermoplastic elastomer containing dynamic covalent bonds; Self-assembly tackifier: 15-25%, wherein the self-assembly tackifier comprises modified rosin acid or short-chain alkyl amide, and forms a dynamic network with the dynamic matrix through weak interactions formed by hydrogen bonding or π-π stacking; Nanoparticle reinforcement material: 5-10%, the nanoparticles are silicon dioxide or aluminum oxide with surface silanization treatment, and the particle size is 10-50 nanometers; Environmentally responsive additives: 1-5%, including thermosensitive polymers or polyvinyl alcohol; Antioxidants and stabilizers: 0.5-1%.

2. The non-residue high-viscosity environmentally friendly tape glue according to claim 1, characterized in that: The dynamic covalent bonds in the dynamic matrix material include acylhydrazone bonds, disulfide bonds or other reversible chemical bonds, and the dynamic matrix also contains flexible segments to enhance flexibility.

3. The non-residue high-viscosity environmentally friendly adhesive tape glue according to claim 1, characterized in that: The self-assembly tackifier forms a dynamic viscous network with weak interaction with the dynamic matrix through hydroxyl, carboxyl or amino polar functional groups, and the network dissociates itself when peeled off.

4. The non-residue high-viscosity environmentally friendly tape glue according to claim 1, characterized in that: The nanoparticles are surface-modified by a silane coupling agent to improve their dispersibility and adhesion properties in a dynamic matrix.

5. The non-residue high-viscosity environmentally friendly tape glue according to claim 1, characterized in that: The environmental response agent includes poly (N-isopropylacrylamide) for adjusting viscosity under temperature change conditions.

6. A method for preparing the non-residue high-viscosity environmentally friendly tape glue according to claim 1, characterized in that: The following steps are involved: Dynamic matrix preparation: The polyurethane matrix material and the dynamic covalent bond monomer are mixed in proportion, and copolymerized at 80-120° C. for 2-4 hours under the action of an organic tin or organic titanium catalyst to form a dynamic matrix, which is then cooled for standby use; Preparation of self-assembly adhesion promoter: The modified rosin acid or short-chain alkyl amide is mixed with a polar solvent in a ratio of 1:2 to 1:5, deionized water is added to promote weak interactions to form a self-assembled network, and the solvent is evaporated by heating to 40-60° C. to obtain a self-assembled tackifier; Dynamic matrix and tackifier compound: The dynamic matrix and the self-assembly adhesion promoter are mixed in a ratio of 3:1 to 5:1, stirred at 50-70°C for 20-40 minutes, and the silanized nanoparticles are added and stirred for 5-15 minutes to ensure uniform distribution; Additive addition and pre-curing: Add environmental response additives and antioxidants, stir at a low speed of 200-400 rpm for 5-10 minutes, and pre-cure at 30-50°C for 1-2 hours; Final curing: The pre-curing mixture is heated to 60-80°C, cured for 2-4 hours, cooled to room temperature and stored to obtain a finished glue.

7. The method according to claim 6, characterized in that The dynamic covalent bond monomers used in the preparation of the dynamic matrix include acylhydrazone bond monomers or disulfide bond monomers, and the addition ratio thereof is 1-10% of the matrix mass.

8. The method according to claim 6, characterized in that In the preparation of the self-assembly tackifier, the mixing ratio of the polar solvent to the tackifier raw material is 1:2 to 1:5, and the solvent volatilization temperature is 40-60°C.

9. The method according to claim 6, characterized in that During the mixing process, the mass ratio of the dynamic matrix to the tackifier is 3:1 to 5:1, the stirring speed is 300-500 rpm, and the stirring time is 20-40 minutes.

10. The method according to claim 6, characterized in that In the final curing step, the curing temperature is 60-80° C. and the curing time is 2-4 hours.